Plant-derived Pembrolizumab in conjugation with IL-15Rα-IL-15 complex shows effective anti-tumor activity - Kaewta Rattanapisit; Pipob Suwanchaikasem; Christine Joy I. Bulaon; Shiying Guo; Waranyoo Phoolcharoen (PLoS ONE, 2025)
Anti-programmed cell death 1 (PD-1) monoclonal antibodies (mAbs) have proven to be effective in treating various cancers, including colorectal, lung, and melanoma. Despite their clinical success, some patients develop resistance to mAbs, requiring co-treatments with radio- or chemotherapy. Interleukin-15 (IL-15) is an immunostimulatory cytokine that promotes immune cell production and proliferation. It has been combined with mAbs and other immunotherapies to improve efficacy and reduce side effects. Fusion of anti-PD-1 mAb and IL-15 streamlines drug administration and management. In this study, we developed a prototype by conjugating the IL-15 receptor subunit alpha (IL-15Rα) and IL-15 complex to the C-terminus of anti-PD-1 Pembrolizumab (Pembrolizumab-IL-15Rα-IL15) using plant molecular farming for production. LC-MS revealed the presence of plant N-glycans (GnGnXF, GnXF and Man9GlcNAc2) on the molecule, which may affect receptor-binding avidity. However, ELISA demonstrated comparable binding efficacy of Pembrolizumab-IL-15Rα-IL15 to human PD-1 protein as commercial Pembrolizumab. In a mouse anti-cancer study, Pembrolizumab-IL-15Rα-IL15 (3 mg kg-1) exhibited slightly improved tumor-growth inhibition, reducing tumor size by 94% compared to commercial Pembrolizumab (5 mg kg-1) with an 83% reduction, regardless of statistically significant difference. In conclusion, Pembrolizumab-IL-15Rα-IL-15 was successfully produced using plant molecular farming and shows promise in addressing mAb drug resistance and enhancing the immunomodulatory effects of IL-15 payload.